The effects of muscle contraction and recombinant osteocalcin on insulin sensitivity ex vivo. Issue 2 (February 2016) - Levinger, I.; Lin, X.; Zhang, X.; Brennan-Speranza, T.; Volpato, B.; Hayes, A.; Jerums, G.; Seeman, E.; McConell, G.
Abstract Summary We tested whether GPRC6A, the putative receptor of undercarboxylated osteocalcin (ucOC), is present in mouse muscle and whether ucOC increases insulin sensitivity following ex vivo muscle contraction. GPPRC6A is expressed in mouse muscle and in the mouse myotubes from a cell line. ucOC potentiated the effect of ex vivo contraction on insulin sensitivity. Introduction Acute exercise increases skeletal muscle insulin sensitivity. In humans, exercise increases circulating ucOC, a hormone that increases insulin sensitivity in rodents. We tested whether GPRC6A, the putative receptor of ucOC, is present in mouse muscle and whether recombinant ucOC increases insulin sensitivity in both C2C12 myotubes and whole mouse muscle following ex vivo muscle contraction. Methods Glucose uptake was examined in C2C12 myotubes that express GPRC6A following treatment with insulin alone or with insulin and increasing ucOC concentrations (0.3, 3, 10 and 30 ng/ml). In addition, glucose uptake, phosphorylated (p-)AKT and p-AS160 were examined ex vivo in extensor digitorum longus (EDL) dissected from C57BL/6J wild-type mice, at rest, following insulin alone, after muscle contraction followed by insulin and after muscle contraction followed by recombinant ucOC then insulin exposure. Results We observed protein expression of the likely receptor for ucOC, GPRC6A, in whole muscle sections and differentiated mouse myotubes. We observed reduced GPRC6A expression following siRNA transfection. ucOC significantly increased insulin-stimulated glucose uptake dose-dependently up to 10 ng/ml, in differentiated mouse C2C12 myotubes. Insulin increased EDL glucose uptake (∼30 %, p  < 0.05) and p-AKT and p-AKT/AKT compared with rest (allp  < 0.05). Contraction prior to insulin increased muscle glucose uptake (∼25 %, p  < 0.05), p-AKT, p-AKT/AKT, p-AS160 and p-AS160/AS160 compared with contraction alone (allp  < 0.05). ucOC after contraction increased insulin-stimulated muscle glucose uptake (∼12 %p  < 0.05) and p-AS160 (<0.05) more than contraction plus insulin alone but without effect on p-AKT. In the absence of insulin and/or of contraction, ucOC had no significant effect on muscle glucose uptake. Conclusions GPRC6A, the likely receptor of osteocalcin (OC), is expressed in mouse muscle. ucOC treatment augments insulin-stimulated skeletal muscle glucose uptake in C2C12 myotubes and following ex vivo muscle contraction. ucOC may partly account for the insulin sensitizing effect of exercise.